Working with Nature in Aotearoa New Zealand: An Ethnography of Coastal Protection - Gesing, Friederike (transcript, 2016)
Working with nature – and not against it – is a global trend in coastal management. This ethnography of coastal protection follows the increasingly popular approach of "soft" protection to the Aotearoa New Zealand coast. Friederike Gesing analyses a political controversy over hard and soft protection measures, and introduces a growing community of practice involved in projects of working with nature. Dune restoration volunteers, coastal management experts, surfer-scientists, and Maori conservationists are engaged in projects ranging from do-it-yourself erosion control, to the reconstruction of native nature, and soft engineering "in concert with natural processes". With soft protection, Gesing argues, we can witness a new sociotechnical imaginary in the making.